Pengaruh MBKM-Kewirausahaan dan Penggunaan Media Sosial Terhadap Minat Berwirausaha Mahasiswa - Shavira Dwita Cahyani; Cicilia Dyah S. Indrawati; Anton Subarno (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to find out: (1) the effect of Independent Learning-Independent Campus program “Entrepreneurship” on entrepreneurship interest of student of Office Administrastion Education Sebelas Maret University, (2) the effect of using social media on entrepreneurship interest of student of Office Administrastion Education Sebelas Maret University, (3) the effect of Independent Learning-Independent Campus program “Entrepreneurship” and using social media on entrepreneurship interest of student of Office Administrastion Education Sebelas Maret University. The research method used correlational with a quantitive approach. Data collection technique carried out by using a questionnaire. Data analysis technique use multiple and basic linear regression analysis. The result showed that: (1) there is significant positive effect of Independent Learning - Independent Campus Program “Entrepreneurship” on entrepreneurial interest (tcount (2,98) > ttable (1,99)); (2) there is significant positive effect of using social media on entrepreneurial interest (tcount (2,18) > ttable (1,99)); (3) there is significant positive effect of Independent Learning - Independent Campus Program “Entrepreneurship” and using social media on entrepreneurial interest (Fcount (6,99) > Ftable (3,11)). The Regression equation obtained is Y = 11,20 + 0,41 X1 + 0,32 X2.